COVID-19 Fear: Factors Impacting Its Reduction and Negative Coping Strategies - Kurapov, Anton; Loshenko, Oleksandra; Bakhvalova, Alina (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2022)
The article is dedicated to the topics of COVID-19 fear factors on the one side and the influence of this fear on using negative coping strategies on the other. The factors that we supposed that influence on COVID-19 fear is passing the COVID-19 test and experiencing COVID-19 symptoms personally or someone’s close symptoms. There was not found any statistical difference in fear of COVID-19 in groups, where closest (friends or relatives) had COVID-19 symptoms or participants tested for the COVID-19. Only in groups of participants that had or had not COVID-19 symptoms we found a statistically significant difference. Half of the group who had the COVID-19 symptoms noted a decrease in COVID-19 fear while participants from another group mostly did not change their degree of COVID-19 fear. Thus, the experience of COVID-19 disease tends to decrease the level of fear. At the same time, there is no significant difference between these groups in general level of COVID-19 fear because this variable does not show changings during time, but only current level of fear. The other side of the article is researching of connection between negative coping strategies and the low resilience level. According to other researches, we chose smoking and cannabis use as negative coping strategies. Participants who used to smoke more than usual because of anxiety about COVID-19 had higher fear of COVID-19 and lower resilience than participants who did not do that. We got the same results for cannabis using, but we need to pay attention to small group volume: only 10 participants, because for students of universities with average high intellect, good education and cultural background this kind of risky behavior is not typical. As a result, in the groups that did not smoke or did not use cannabis as type of coping with COVID-19 anxiety (or even did not do it at all) the resilience level was higher and level of COVID-19 fear was lower, than in groups with such a negative copings. Also, we found statistically significant differences between more frequent smoking or non-smoking male groups in resilience and COVID-19 fear level, when in women groups there was not such a difference.